Seminal Plasma: Effect on Motility, Membrane Functionality, and Spermatic Chromatin Dispersion of Equine Sperm Treated with N-acetyl-L-cysteine at 5°C - Rodrigues, Murilo Farias; Trentin, Janislene Mach; Araujo, Laurence Boligon de; Centeno, Luiz Augusto Machado; Schenatto, Ricardo Olimpio; Pessoa, Gilson Antonio; Neves, Adriana Pires; Rubin, Mara Iolanda Batistella (Acta Scientiae Veterinariae, 2016)
Background: N-acetyl-L-cysteine (NAC) is a low molecular weight thiol studied as an antioxidant for stallion semen preservation without changes on sperm viability. Equine seminal plasma is rich in sulfur proteins (cysteine residues) named CRISPS, which, when combined with sulfur-containing antioxidants, can enhance the appearance of DNA lesions. The aim of this study was to assess and compare the effect of different concentrations of NAC by evaluating motility, membrane function and sperm chromatin integrity of equine semen cooled at 5°C in 50% of seminal plasma. Materials, Methods & Results: Nine ejaculates from 9 stallions were divided into 4 aliquots, diluted and divided in nonsupplemented skim milk group (0.0 mM), or supplemented with 5.0, 2.5 and 0.5 mM NAC. Evaluations were made at 0 h, 24 h and 48 h of cooling, except for motility which was evaluated only up to 24 h. The 0.5 (59.7 μM2) and 5.0 mM NAC (55.5 μM2) groups showed similar areas of sperm chromatin dispersion among all groups. However, the area of chromatin dispersion between the non-supplemented group was higher = 65.3 μM2 than the group supplemented with 2.5 mM. The percentage of cells with a functional plasma membrane was similar between supplemented and non-supplemented (0.0 mM) groups, but higher (P < 0.05) in the 0.5 mM NAC (39.7 and 39.8%, respectively) than that of 2.5 mM (34.5%) and 5.0 mM (34.2%) concentrations. Progressive motility was similar among all groups supplemented with NAC. The 0.5 mM NAC group showed 35.2% motile cells while the non-supplemented group exhibited 36.2%. Although 50% seminal plasma was used, NAC did not affect sperm chromatin integrity. Discussion: Seminal plasma interfered more in the results of different concentrations of NAC. This statement is proven by the motility analysis where all NAC concentrations showed similar results. Plasma percentage higher than 20% in diluted semen causes deleterious effects on sperm, such as decreased motility and fertilizing capacity. The membrane analysis in our study was compromised because NAC (2.5 to 5.0 mM) showed high osmolarity. As this was not adjusted, it affected the result. The 2.5 mM NAC group showed a lower area of sperm chromatin dispersion than none-treated sperm, although showing similar results to the other treatments. In a study with semen of Mangalarga Marchador stallions, the 2.5 mM of NAC was able to protect sperm membrane integrity. However, in another study, where semen was kept cooled between 5 and 15°C, no change was observed on sperm quality over different concentrations of NAC. This reinforces that 2.5 mM of NAC provides adequate protection to semen exposed to harmful conditions.The high percentage of plasma associated with this sulfur antioxidant did not compromise DNA integrity, as NAC concentration used was 100 times less than the concentration needed to induce DNA lesions.